Facts on Relationship Between Corruption and Organized Crime (Kriminalističke teme, 2007)
This article deals with the relationship between corruption and organized crime. Corruption and organized crime are commonly referred to as interrelated, almost complementary phenomena. From the point of view of their magnitude, as well as detrimental effects they exert on normal functioning of society (e.g. feelings of insecurity and distrust in governance), corruption and organized crime are both characterized by ubiquity, making them problems of global concern). The public tends to uncritically relate each and every case of corrupt behavior with organized crime, implying an illicit connection between organized crime and government structures. We briefly look at the different (criminological) approaches in defining both of the phenomena, then give greater critical attention to the relation between the two. We do so by describing the results of empirical studies in European countries over the last decade.